Gender Relations, Gender Equity, and Community Sports Spaces. (December 2021) - Jeanes, Ruth; Spaaij, Ramòn; Farquharson, Karen; McGrath, Georgia; Magee, Jonathan; Lusher, Dean; Gorman, Sean
This study employs a spatial analysis to critically examine gender relations within an Australian football and netball community sports club that has sought to address gender inequity and promote the participation of women across the club. Notable changes included increased female representation in the club's decision-making structures, growing numbers of female members, and the establishment of a women's and girls' football section. Using an in-depth case study that combined interviews and observations over a 6-month period, we investigated the impact these changes have had on transforming gender relations and in challenging perceptions of the club as a privileged space for its male members. The study utilized spatial and feminist theory to illustrate that, despite the club's efforts to change gender relations, men who are able to embody dominant forms of masculinity (i.e., high ability and able-bodied) continue to be privileged within the club environment. The article highlights the importance of spatial analysis in illuminating the ways in which various micro-level practices preserve dominant gender relations within community sports. The findings reinforce that although a greater number of women and girls are participating in community sport, this alone is not significantly reshaping gender relations. Policies seeking to promote gender equity in sport need to enforce changes in club environments in addition to focusing on increasing women's participation.